(untitled) (Nigerian Journal of Technology, 2016)
Rice husk ash (RHA) is an agro waste and a natural pozzolana which is rich in silica and found in abundance globally. This research considered the pozzolanic properties of RHA from Seven different sources in Nigeria (Ogoja, Abakaliki, Adani, Adikpo, Obubra, Makurdi and Vandikya). It is discovered that the elemental chemical composition of this natural pozzolan varies based on their location. Samples from Ogoja were found to have the highest pozzolanic properties followed by Abakaliki, Adani, Adikpo, Obubra, Makurdi and Vandikya. Their silica content was found to be84.55%, 76.3%, 70.12%, 70.11%, 64.67%, 55.55%, and 48.4% respectively. Four out of the seven samples with the highest pozzolanic values were used as partial replacements for ordinary Portland cement at 5, 10, 15, 20, 25, and 30% replacement levels. Concrete mix ratio of 1:1.5:3 was adopted and the compressive strength values at 28 days were found to be in the range of 37-42N/mm2 at 5%RHA, 35-39.5N/mm2 at 10%RHA, 30-34.5N/mm2 at 15%RHA, 27-29N/mm2 at 20%RHA, 22-25.6N/mm2 at 25% RHA and 21-24N/mm2 at 30% RHA compared to the controlled sample with a strength value of 42.64N/mm2. http://dx.doi.org/10.4314/njt.v35i4.1